The Influence of Production Factors on Carrot Farming Production and Income : Case Study: Sugihen Village, Dolat Rakyat District, Karo Regency, North Sumatra - Simatupang, Aditia Erick Cantona; Simatupang, Jones T; Hutapea, Kenal P; Sinaga, Masni Ester S (Journal of Agriculture, 2024)
This research aims to determine the influence of production factors on carrot farming production in the research area to determine the influence of production factors on the income of carrot farmers in the research area, to determine the level of feasibility of carrot farming in the research area; to determine the level of optimization of workforce deployment for carrot farming in the research area. The regional determination was carried out purposively in Sugihen Village, Dolat Rakyat District, Karo Regency. The research sample was set at 30 samples of farmers, where sampling was carried out using Simple Random Sampling. The research results show that simultaneously, land area, labor expenditure, and production facility costs significantly affect carrot farming production, with R2 = 0.936. Partially, land area and production facility costs substantially affect production, but labor does not considerably impact carrot farming production. Simultaneously, land area, labor expenditure, and production facility costs significantly affect carrot farming income with R2 = 0.900. Partially, land area and production facility costs substantially affect income, but labor has no significant effect on carrot farming income. Carrot farming has economic feasibility with an RCR value = 4.41, so carrot farming in the research area is worth pursuing. The optimal level of labor expenditure in carrot farming is -1.97. So that NPMX < 1, the expenditure of labor is not optimal, and to achieve maximum profits, the expenditure of labor in carrot farming must be reduced.